Intravascular lithotripsy in calcified peripheral lesions: the real-world single-center JEN-experience. (14th October 2021) - Kretzschmar, D; Aftanski, P; Thieme, M; Schulze, P C; Moebius-Winkler, S
Abstract: Objective: Peripheral vascular disease (PVD) is a major cause of morbidity and mortality with increasing need for interventional therapies. Vascular calcification increases risk of complications and may impair the effect of antiproliferative therapy. Intravascular lithotripsy (IVL) using pulsatile sonic pressure waves to modify intimal and medial calcium is a promising approach for those patients to overcome the drawbacks of vascular calcification. Purpose: A single-center, prospective registry of patients undergoing peripheral lithotripsy was established. Periprocedural safety events as well as short and long term follow-up clinical data were evaluated. Methods: A prospective review of cases using IVL was performed for the period from December 2018 to January 2021 at our center. Angiographic images were quantified by using the QVA 8.0 module, Medis Suite Version 3.2.60.4 developed by Medis Imaging Systems. Results: 61 cases of IVL were performed in 51 patients with Rutherford class 3. Mean age was 71 years with 78% (28) of the patients being men. Diabetes was present in 80% and renal insufficiency in 47% of the cases. The median calcified lesion length treated was 82 mm (10; 390 mm) with a PACCS sore of 3 (1; 3), indicating a highly calcified status. In 41% (n=25), predilation was necessary. We treated 8 iliac-, 19 common femoral-, 52 superficial femoral-, 5 deep femoral-, 29 popliteal- and 2 crural- lesions with balloon sizes ranging from 4.0 to 7.0 mm. In 35 (57%) cases IVL was used as a stand-alone therapy, in the remaining 26 an adjunctive therapy (DCB and/or stent) was used. We were able to reach an acute luminal gain of 2.5 mm. A ballon rupture occurred in 6 (10%) cases. There were no other complications. Mean ABI improved from 0.6 to 0.8 (p<0.0001) immediate after the intervention. Follow-up after 6 months again demonstrated an improved ABI of 0.8 (p<0.0001 vs. baseline). Conclusion: This first real-world data of IVL reports compelling safety of IVL in a complex, difficult-to-treat patient cohort. For the first time, clinical follow-up data were presented and demonstrated a sustained improved ABI after 6 months. This innovative approach will gain more interest in the future, especially since long term effects of paclitaxel eluting devices are controversially discussed. Funding Acknowledgement: Type of funding sources: None.